HUBUNGAN KEBERSIHAN DAPUR DAN KONSTRUKSI RUMAH DENGAN KEBERADAAN TIKUS DI RUMAH WARGA DUSUN MAJAPAHIT KELURAHAN KALIERANG KECAMATAN BUMIAYU KABUPATEN BREBES TAHUN 2018 - Devi Widya Arianti; Djamaluddin Ramlan; Budi Utomo (Buletin Keslingmas, 2019)
Basically, the house has important role for human as their living place in order to fulfill their basic necessary and it is a citizen health determiner. The kind of this research is observational cross sectional approach. The method used is observation and interview directly on the respondent. Data analysis using table analysis, that is analyzed descriptively. As the result, it is known that from 86 houses, there are 52 houses (60.5%) with clean kitchen, 34 houses (39.5%) with dirty kitchen, 38 houses (44.2%) with house construction which is closed of mouse, and 48 houses (33.7%) with house construction which is not closed of mouse. The conclusion of this research is based on statistic test by using Chi-Square test, it is resulted sig score in the amount of 0.00 so sig0.005 means that there is relation between house construction and kitchen cleanness with mouse existence. Suggestion should always clean the kitchen from leftover food / food and other scattered waste, construction of a house that has not been tightly mice to make a tight house construction rats